Well-Behaved Variants Seldom Make the Apparatus: Stemmata and Apparatus in Digital Research. Issue 1 (15th December 2021) - Bordalejo, Barbara
Abstract : This article describes computer-assisted methods for the analysis of textual variation within large textual traditions. It focuses on the conversion of the XML apparatus into NEXUS, a file type commonly used in bioinformatics. Phylogenetics methods are described with particular emphasis on maximum parsimony, the preferred approach for our research. The article provides details on the reasons for favouring maximum parsimony, as well as explaining our choice of settings for PAUP. It gives examples of how to use VBase, our variant database, to query the data and gain a better understanding of the phylogenetic trees. The relationship between the apparatus and the stemma explained. After demonstrating the vast number of decisions taken during the analysis, the article concludes that as much as computers facilitate our work and help us expand our understanding, the role of the editor continues to be fundamental in the making of editions.